Planning for autonomy and conservation: ‘Life Plans’ and communal reserves in the Amazonian borders of Peru - (:unkn) unknown (Taylor & Francis, 2024)
State-promoted biodiversity conservation can either align with or diverge from Indigenous Peoples’ priorities, knowledge, and self-determined development paths. Drawing on fieldwork at the Amazon borders of Brazil, Colombia, Ecuador, and Peru, this pap...
Keywords: Autonomía indígena; Amazonía peruana